Victims and Survivors in the Rape-Revenge Narrative: A Comparison of Black Christmas (2019) and I May Destroy You (2020) - Michaela Keating (CINEJ Cinema Journal, 2022)
The rape-revenge narrative is fertile ground to explore and contextualize the experience of sexual violence and its aftermath. While typically a trope in genre films seen through the male gaze, female filmmakers are reclaiming this narrative. Two recent entries from female filmmakers into the canon of the rape-revenge fantasy are the 2019 horror remake Black Christmas, and the 2020 HBO drama-comedy series I May Destroy You. This article will compare the ways that these two examples construct characters who experience rape, and how their personality traits and behaviors are infused with the cultural perceptions of "rape victims" or "rape survivors." This analysis will be grounded in ongoing feminist discourse around the use of the term applied to those who experience rape, and how this impacts our understanding of these characters.